MALARIA ERADICATION AND ITS TECHNICAL, OPERATIONAL AND ADMINISTRATIONAL PROBLEMS IN IRAN - AV. Manouchehri; B. Janbakhsh (Tehran University of Medical Sciences, 1977)
Malaria has always been regarded as one of the most important health problems with which Iran is faced. Most parts of the country, especially densely populated areas, were known as malarious areas. Records of 1947 show that 25% of cases referred to health centers and dispensaries of the Ministry of Health were due to malaria in Khuzestan and Caspian Sea areas. The mortality rate of malaria in the Khuzestan and Caspian littoral areas and Khuzestan province was reported to be about Caspian littoral areas and Khuzestan province was reported to about 30-40% of total deaths. It has been estimated that each year the number of malaria cases was between 4-5 millions. At present 2/3 of the country with a population of 23 millions is under consolidation phase and the number of positive cases in this area was 4312 in 1976. In the Southern part of Iran, which has a tropical climate with the average temperature ranging between 12-50 and the average relative humidity between 40- 50%, the malaria campaign has not been as successful as in the Northern parts. In this part of the country our malaria eradication program is faced with technical problems such as malaria eradication program is faced with technical problems such as resistance of A. stephensi to organochlrine insecticides. The development of DDT and dieldrise the resistance by A. stephensi in 1957 and 1959 practically stopped the eradication of malaria in subsequent years in this part of the country. In October 1967, the Southern part of the country with a population of about 4 millions was sprayed with malathion 2-3 times per year. This spraying was supported by monthly positive case detection, treatment of positive cases, introduction of Gambusia fish in active and potential breeding places and mass - drug administration. In the first 4 years of this campaign the annual parasite incidence came down from 8.41 per thousand to 2.1 per thousand.